The H+-pyrophosphatase IbVP1 regulates carbon flux to influence the starch metabolism and yield of sweet potato. (1st February 2021) - Fan, Weijuan; Zhang, Yandi; Wu, Yinliang; Zhou, Wenzhi; Yang, Jun; Yuan, Ling; Zhang, Peng; Wang, Hongxia
Abstract: Storage roots of sweet potato are important sink organs for photoassimilates and energy, and carbohydrate metabolism in storage roots affects yield and starch production. Our previous study showed that sweet potato H + -pyrophosphatase (IbVP1) plays a vital role in mitigating iron deficiency and positively controls fibrous root growth. However, its roles in regulating starch production in storage roots have not been investigated. In this study, we found that IbVP1 overexpression in sweet potato improved the photosynthesis ability of and sucrose content in source leaves and increased both the starch content in and total yield of sink tissues. Using 13 C-labeled sucrose feeding, we determined that IbVP1 overexpression promotes phloem loading and sucrose long-distance transport and enhances Pi-use efficiency. In sweet potato plants overexpressing IbVP1, the expression levels of starch biosynthesis pathway genes, especially AGPase and GBSSI, were upregulated, leading to changes in the structure, composition, and physicochemical properties of stored starch. Our study shows that the IbVP1 gene plays an important role in regulating starch metabolism in sweet potato. Application of the VP1 gene in genetic engineering of sweet potato cultivars may allow the improvement of starch production and yield under stress or nutrient-limited conditions.